Linking Palliative Homecare to the Universal Health Coverage Principles and the United Nations Sustainability Development Goals Using the i Frameworks Strategic and Social Requirements Modelling Applied to a Cancer Care Organisation - Odeh, Yousra; Tbaishat, Dina; Kharbat, Faten; Shamieh, Omar; Odeh, Mohammed (International arab journal of information technology, 2023)
Adherence to the Universal Health Coverage (UHC) principles in relation to palliative care is a key WHO directive to attain as a right for every citizen. However, UHC principles have been observed to be hindered by several barriers. Moreover, the UNSDGs, and in particular the UNSDG 3, demands “Good Health and Well Being” with the two key indicators UNSDG 3.8.1 and 3.8.2 that can be considered as metrics to assess governance conformance to palliative care. This paper reports on addressing the current research gap in linking the UHC principles to UNSDGs and, in particular, UNSDG3 and the WHO identified Palliative Care Barriers (PCB) using the i* framework Strategic Dependency (SD) and Strategic Rationale (SR) models applied to Home Healthcare Care (HHC) of a regional cancer care organisation, namely King Hussain Cancer Center (KHCC). Building on our i* HHC SD and SR developed models, and for HHC being an essential and critical part of palliative care, an integrated framework has been developed that not only links UHC principles and WHO barriers of palliative care to UNSDG 3, but a full network of dependencies that facilitates observing the linkages and impact of the most critical and strategic actors in HHC on the UHC, barriers to palliative care and UNSDG 3. Furthermore, such highly comprehensive UHC-PCB-UNSDG-i* framework network instantiations have led to identifying patterns of categories or groups of associations between UNSDG3 KPIs, UHC principles, WHO palliative care barriers and HHC actors. Hence, this contributes to healthcare policy and decision makers to revisit their policies, plans, budgets, and constraints for the deficiencies in the qualitative satisfaction of the universal health coverage principles and how palliative care barriers can be alleviated in association with the actors in the i* SD and SR models and associated goals, tasks and resources. A further corollary of this research is that change impact analysis can be timely attained to study the impact of a change driven by updating goals, tasks, and resources of the i* model to improve adherence to the UNSDG3 KPIS and UHC principles. Finally, this work has inspired work in progress to develop a data analytics platform from the evolving instances of applying palliative care processes using the resultant UHC-PCB-UNSDG-i* framework